12 Comparison of Normal Saline, Hypertonic Albumin and Hypertonic Albumin Plus Terlipressin Resuscitation in an Infant Animal Model of Hypovolemic Shock. (October 2012) - Urbano, J; González, R; Solana, MJ; López, J; Botrán, M; García, A; López-Herce, J
Abstract : Background and aims: To determine if in an infant animal model of hemorrhagic shock, hypertonic albumin plus single bolus of terlipressin, as opposed to isotonic crystalloid, would improve global hemodynamic and perfusion parameters. No previous experience in children or infant animal models has been reported. Methods: Prospective, randomized study in 30 two month-old piglets (9.9±2kg). Following mechanical ventilation, hypovolemia was induced by controlled 30 ml/kg bleed. After 30′ pigs randomly received: Normal Saline (NS) 30 ml/kg, n=10, Albumin 5% plus Hypertonic 3% Saline (AHS) 15 ml/kg, n=10, or single bolus of terlipressin 20 µg/Kg iv plus AHS (TAHS) 15 ml/kg, n=10, over 30 min. Heart rate (HR), mean arterial pressure (MAP), cardiac index (CI), brain tissue oxygenation by near infrared spectroscopy (bTOI), internal carotid artery flow (ICAF), arterial lactate and intramucosal gastric pH (pHi) were compared by ANOVA. Results: 30' after bleeding as well as 30', 60' and 90' after infusion no significant differences between groups were observed. However, 90' after infusion the TAHS group presented trends towards higher MAP (NS: 71±8, AHS: 74±7, TAHS: 82±7 mmHg); CI (NS: 3.2±0.3, AHS: 3.8±0.3, TAHS: 4.2±0.3 L/min/m 2 ); lactate (NS: 1.7±1.7, AHS: 0.8±1.4, TASH: 3.6±1.4 mmol/L); bTOI (NS: 42±5, AHS: 45±4, TASH: 48±6%); and ICAF (NS: 41±4, AHS: 42±4, TASH: 48±3 mL/min); with no differences in HR (NS: 166±11, AHS: 145±10, TAHS: 159±9 bpm); and pHi (NS: 7.1±0.1, AHS: 7.2±0.1, TASH: 7.2±0.1). Conclusion: All fluids achieved similar hemodynamic and perfusion endpoints without a significant improvement secondary to the use of terlipressin.